PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG MENGGUNAKAN JASA PEMBIAYAAN KREDIT KENDARAAN BERMOTOR RODA DUA DI PT. FEDERAL INTERNATIONAL FINANCE AIR MOLEK - Nadeak, Niko Ardian; Deliana, Evi; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
PT. Federal International Finance Air Molek has violated Article 7 letter (d) for notperforming an obligation by offering services that are not in accordance with Article 17paragraph 1 letter (a) of the Financial Services Authority Regulation Number 29 of 2014concerning the Implementation of Business Financing Companies regarding Advances forVehicle Financing motorized two wheels. And in offering financing services, PT. FederalInternational Finance Air Molek also does not carry out its obligations or provide consumerrights based on Act Number 8 of 1999 concerning Consumer Protection. The purpose of writingthis thesis, namely: First, In order to know the legal protection of the rights of consumers whouse two-wheeled vehicle loan financing services related to the provision of down payments ofunder 20% at Federal International Finance Air Molek. Second, to be aware of the legalconsequences caused to consumers who use two-wheeled motor vehicle loan financing servicesrelated to the provision of down payments of under 20%.This type of research is a type of sociological legal research. This research was conductedat PT. Federal International Finance branch of Air Molek, Pasir Penyu District, Indragiri HuluRegency, Riau Province. Sociological law research uses primary data and secondary data, whilethe population and sample are the parties related to the problem examined in this study. Datacollection techniques in this research were interviews and literature study.From the results of the research problem there are two main things that can be concluded.First, the Financing Company of PT. Federal International Finance does not provide consumerrights regarding the provision of true, clear and honest information about advances offered forfinancing services that are not in accordance with article 17 paragraph 1 of the FinancialServices Authority Regulation Number 29 of 2014. Second, the consequences arising from thegranting of motorized vehicle credit two related to a down payment of under 20% at PT. FIF ismostly caused by consumers, such as being unable to pay monthly installments, lost objects,transfer of objects without the knowledge of the finance company which in this case results indisruption of financing experienced by PT. Federal International Finance, this is due to lack ofinformation regarding financing agreements, and financing agreements offered by PT. FederalInternational Finance is not in accordance or contrary to the legal terms of the agreement, thenthe financing agreement is considered null and void, meaning that from the beginning theagreement was considered to have never existed.Keywords: Consumer Protection - Financing Services - Advance Financing - FinancingAgreement - PT. Federal International Finance